And there was light : Abraham Lincoln and the American struggle - Meacham, Jon (New York : Random House, 2022)
"A president who governed a divided country has much to teach us in a twenty-first-century moment of polarization and political crisis. Abraham Lincoln was president when implacable secessionists gave no quarter in a clash of visions inextricably bound up with money, power, race, identity, and faith. He was hated and hailed, excoriated and revered. In Lincoln we can see the possibilities of the presidency as well as its limitations. At once familiar and elusive, Lincoln tends to be seen in popular minds as the greatest of American presidents--a remote icon--or as a politician driven more by calculation than by conviction. This illuminating new portrait gives us a very human Lincoln--an imperfect man whose moral antislavery commitment was essential to the story of justice in America. Here is the Lincoln who, as a boy, was steeped in the sermons of emancipation by Baptist preachers; who insisted that slavery was a moral evil; and who sought, as he put it, to do right as God gave him light to see the right. This book tells the story of Lincoln from his birth on the Kentucky frontier in 1809 to his leadership during the Civil War to his tragic assassination at Ford's Theater on Good Friday 1865: his rise, his self-education through reading, his loves, his bouts of depression, his political failures, his deepening faith, and his persistent conviction that slavery must end. In a nation shaped by the courage of the enslaved of the era and by the brave witness of Black Americans of the nineteenth century, Lincoln's story illuminates the ways and means of politics, the marshaling of power in a belligerent democracy, the durability of white supremacy in America, and the capacity of conscience to shape the maelstrom of events"--
Prologue: A big, inconsistent, brave man -- Part I: Clothed in bone & nerve, beginnings to 1846. My mind and memory ; Abe was hungry for books ; I am humble Abraham Lincoln ; Founded in injustice and bad policy ; She had the fire, will, and ambition -- Part II: The banner he bears, 1846-1859. From the very depths of society ; We have got to deal with this slavery question ; The conscience of the nation must be roused ; To understand the moral universe ; If all earthly powers were given to me ; The hateful embrace of slavery ; By white men for the benefit of white men -- Part III: Right makes might, 1859-1861. Let us dare to do our duty ; God help us, God help me ; He has a will of his own ; To take the Capital by violence -- Part IV: My whole soul is in it, 1861-1863. The momentous issues of civil war ; "A white man's war" ; My boy is gone--he is actually gone ; I think the time has come now ; The President has done nobly -- Part V: A new birth of freedom, 1863-1864. That all men could be free ; Who shall be the next president? ; The strife of the election -- Part VI: His illimitable work, 1864 to the end. This great moral victory ; The Almighty has his own purposes ; Old Abe will come out all right ; Lincoln was slain; America was meant ; I see now the wisdom of his course
Includes bibliographical references (pages 423-634) and index
Keywords: Lincoln, Abraham, -- 1809-1865; Lincoln, Abraham, -- 1809-1865 -- Views on slavery; Lincoln, Abraham, -- 1809-1865 -- Religion; Presidents -- United States -- Biography; Slavery -- Political aspects -- United States -- History -- 19th century; Slaves -- Emancipation -- United States; United States -- Race relations -- History -- 19th century; United States -- Politics and government -- 1861-1865; United States -- Politics and government -- 1845-1861; Biographies